Fire can weaken or trigger functional responses of trees to flooding in wetland forest patches. (2nd June 2019) - de Almeida Souza, Allan H.; Batalha, Marco Antônio; Casagrande, José Carlos; Rivaben, Rodrigo Cyrino; Assunção, Vivian Almeida; Pott, Arnildo; Alves Damasceno‐Junior, Geraldo
Abstract: Question: Fire and flood act as ecological filters on vegetation, either separately or combined, and cause morphological and physiological changes. Hence, they influence the composition and structure of plant communities. Since evidence strongly suggests that they are important filters operating in the system, we asked if fire, flood intensity, and their interaction could be related to variation in the functional traits of studied trees. Study Site: Pantanal, Mato Grosso do Sul, Brazil. Methods: We sampled 14 individuals (totaling 280) of the 20 most representative trees in 24 forest patches along the flooding gradient and measured functional traits related to allocation of resources and protection in response to these filters. We also assessed leaf and soil nitrogen, phosphorus, and potassium levels. Results: Along the flooding gradient, the studied tree species showed a tendency toward decreasing specific leaf area (SLA), as well as leaf nitrogen concentrations, whereas leaf thickness and leaf dry matter content (LDMC) increased. In burned areas, LDMC and leaf nitrogen exhibited the opposite tendency and decreased along the flooding gradient. Leaf thickness (LT) showed less increase in burned areas, while SLA had less decrease. Relative Bark Thickness (RBT) increased along the flooding gradient only after fire. Soil nitrogen decreased along the flooding gradient without an effect of fire. Conclusions: Since LDMC is a proxy of flammability, the probability of burning decreases after each fire event, while the most flooded environments become less fire‐prone. In burned environments, the differences in the allocation of resources (SLA and LT) diminish along the flooding gradient, indicating that leaf behavior is almost the same post‐fire. RBT increases with increased flooding only after a fire, contributing to oxygen exchange during floods to protect the bark against fire. The interaction between fire and flood causes tree species to invest in structures for protection and resistance to fire, as well as retain nutrients. Abstract : Our study shows variation in functional traits along the flooding gradient with fire influence. Measuring functional traits in burned and unburned forested flooding gradient, we verified that traits vary in response to flood, but fire can soften, invert or even trigger the response to flood. This work is an important step in studies on fire and flood interactions in tree communities in wetlands.